Ljepotica je ukrotila zvijer (O vuku i liji u "Svetoj knjizi vukodlaka" Viktora Pelevina) - Vojvodić, Jasmina, profesorica ruske književnosti (Array, 2012)
The text of Beauty has Tamed the Beast tells of the relationship between the Wolf (a werewolf) and the Fox who, in the guise of a man and an animal, are the main protagonists of Pelevin's novel.